Implementasi Metode Tutor Sebaya dalam Mengatasi Kesulitan Membaca Al-Qur’an Siswa di SMKN 4 Palangka Raya - Lutfi Almadani; Zainap Hartati; Neela Afifah (Jayapangus Press, 2025)
This research is based on the background of students' suboptimal ability to read the Qur'an and their inadequate understanding of the rules of tajweed. This study aims to describe the implementation of peer tutoring methods and identify the factors that support and inhibit them. Using a descriptive qualitative methodology, data was collected systematically through observation, interviews, and documentation. The results of the study show that the implementation of the peer tutor method includes a sequence of three phases of planning, implementation and evaluation. The supporting factors obtained in this study include, high motivation from tutors and tutees, qualified tutors' ability to read and teach the Qur'an, as well as tutors' confidence that is able to foster the spirit of learning tutee, adequate learning facilities, conducive learning atmosphere, close relationship between tutors and tutees, effective small group divisions, variety of interesting learning methods, as well as praise and appreciation from teachers and tutors. The inhibiting factors include, lack of commitment and consistency among some tutors, limited guidance time, and lack of seriousness in learning due to too relaxed relationships. Broadly speaking, the peer tutor method shows good results in creating a collaborative and supportive learning atmosphere in overcoming students' difficulties in reading the Qur'an.